Pengaruh Penerapan Good Corporate Governance, Budaya Tri Hita Karana dan Sistem Informasi Akuntansi Terhadap Kinerja Manajerial - Juniari, Putu Diah Eka; Putra, I Putu Deddy Samtika (Hita Akuntansi dan Keuangan, 2024)
This study intends to ascertain the impact of implementing tri hita karana culture, accounting information systems, and effective corporate governance on the performance of management in village credit institutions (LPD) throughout Blahbatuh District. The population for this study consisted of all 171 LPD personnel in the Blahbatuh District who were registered at LPLPD Gianyar. Samples were taken using the purposive sampling technique, and 124 respondents were gathered. Multiple linear regression analysis, a t test, and a F test were used to analyze the data. The investigation' findings revealed that Tri Hita Karana culture, effective company governance, and accounting information systems all had an important and beneficial effect on managerial performance.